2011
DOI: 10.1192/apt.bp.108.006510
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and neuropsychiatric comorbidities

Abstract: SummaryEpilepsy is a common neurological condition with wide-ranging neuropsychiatric manifestations. The relationship between epilepsy and psychiatry has been recognised for centuries. However, the wide range of neuropsychiatric comorbidities and their extent is only now beginning to be appreciated. The impact of these comorbidities on patients' help-seeking behaviour, seizure control and quality of life suggests that early detection and treatment are of paramount importance. Clinical issues in relation to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
1
16
1
Order By: Relevance
“…It has also been reported that studies in clinical settings have a higher rate of psychiatric morbidity than those carried out within the general population. 33 The rate of psychiatric disorders in our study is, however, lower than the United States studies by Victoroff 34 and Silberman et al . 35 where prevalence rates of 70% and 71% were obtained, respectively.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…It has also been reported that studies in clinical settings have a higher rate of psychiatric morbidity than those carried out within the general population. 33 The rate of psychiatric disorders in our study is, however, lower than the United States studies by Victoroff 34 and Silberman et al . 35 where prevalence rates of 70% and 71% were obtained, respectively.…”
Section: Discussioncontrasting
confidence: 71%
“…It was mentioned by Agrawal and Govender as part of the factors recognized to increase the risk of developing psychopathology in patients with epilepsy. 33 Likewise, in a Nigerian study, it was reported that felt stigma is among the predictors of anxiety and depressive disorders in patients with epilepsy. 13 In our study, discrimination which was experienced by about a third of the studied population was significantly associated with the presence of psychiatric disorder in the first stage analysis but loss this significance at the level of logistic regression.…”
Section: Discussionmentioning
confidence: 98%
“…An increase in seizure susceptibility is a co-morbidity frequently associated with NDDs (Agrawal and Govender, 2011). In addition, similar to described above changes in DF GABA and alterations in synaptic activity were reported in different animal models of NDD (Tyzio et al, 2014;Deidda et al, 2015;Banerjee et al, 2016).…”
Section: Altered Vocalization and Social Interactions In Kcc2 E/+ Micesupporting
confidence: 79%
“…Antecedent central nervous system injury (including stroke, trauma, and brain infection) may lead to hippocampal volume deficient and then cause the onset of epilepsy and schizophrenia (Schmitt, Malchow, Hasan, & Falkai, ). Other factors, like stress during development, depression, and anti‐epileptic drug effects on mental state, are all important contributor to the comorbidity (Agrawal & Govender, ; Barnes & Paolicchi, ). Deeper understanding on the direct pathway from these environmental risk factors to two phenotypes has to await future studies.…”
Section: Discussionmentioning
confidence: 99%